1989
DOI: 10.1149/1.2096373
|View full text |Cite
|
Sign up to set email alerts
|

Copper Photodeposition on TiO2 Studied with HREM and EXAFS

Abstract: The possibility of direct selective surface activation by photodeposition of autocatalytic Cu particles on photosensitive TiO2 substrates in an alkaline electroless copper solution has been investigated. The nucleation and growth of particles were characterized by transmission electron microscopy (TEM). Ex situ high resolution TEM and in situ extendedx-ray absorption fine structure (EXAFS) spectroscopy were used to determine the oxidation state of photodeposited particles on thin polycrystalline TiO2 films and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The first papers about Cu/TiO 2 systems were mainly connected with photodeposition of copper on titania surface as the efficient method for Cu removal from water environments [29][30][31][32]. Cu II ions were reduced to metallic copper with the participation of photogenerated electrons (e − ) and holes (h + ) according to the following Reactions (1) …”
Section: Presence Of Copper Ions In the Tio 2 Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first papers about Cu/TiO 2 systems were mainly connected with photodeposition of copper on titania surface as the efficient method for Cu removal from water environments [29][30][31][32]. Cu II ions were reduced to metallic copper with the participation of photogenerated electrons (e − ) and holes (h + ) according to the following Reactions (1) …”
Section: Presence Of Copper Ions In the Tio 2 Suspensionmentioning
confidence: 99%
“…However, Jacobs et al showed that photodeposition of zero-valent Cu particles was possible and was preceded by photodeposition of Cu 2 O particles [32].…”
Section: Presence Of Copper Ions In the Tio 2 Suspensionmentioning
confidence: 99%
“…Under UV irradiation, the Cu/ZnO (bandgap of 3.18 eV) absorbed the photons efficiently and was excited to form electrons in the conduction band (CB) and holes in the valance band (VB). Theoretically, Cu 2+ ions are reduced to Cu metal and Cu 2 O, which are deposited on ZnO surface in solution under UV irradiation [52]. The standard reduction potential of Cu 2+ /Cu and Cu 2+ / Cu + are + 0.35 V and + 0.15 V versus NHE, respectively [53, Intensity (a.u.…”
Section: Cr(vi) Reduction Mechanismmentioning
confidence: 99%
“…[141][142] Photodeposition has been utilized for removal of metal ions from aqueous environments with semiconducting WO 3 or TiO 2 as photoactive substrates. 48,50,[143][144][145][146] In addition to environmental remediation, photo-assisted deposition can also function as a potentially facile, low-temperature method to modify photoactive surfaces such as TiO 2…”
Section: Discussionmentioning
confidence: 99%